2011
DOI: 10.1038/nature10194
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory transmission from the amygdala to nucleus accumbens facilitates reward seeking

Abstract: The basolateral amygdala (BLA) plays a crucial role in emotional learning irrespective of valence1–5. While the BLA projection to the nucleus accumbens (NAc) is hypothesized to modulate cue-triggered motivated behaviors4, 6, 7,, our understanding of the interaction between these two brain regions has been limited by the inability to manipulate neural circuit elements of this pathway selectively during behavior. To circumvent this limitation, we used in vivo optogenetic stimulation or inhibition of glutamatergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
704
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 774 publications
(738 citation statements)
references
References 26 publications
29
704
3
2
Order By: Relevance
“…Human electrophysiological studies showed a dynamic interaction between the striatum and medial frontal cortex underlying reward-guided learning and decision-making (Cohen, 2007;Cohen et al, 2009). The amygdala was reported to facilitate reward-seeking behaviors by the glutamatergic or dopaminergic neurotransmission in the amygdala-striatum pathway (Lintas et al, 2011;Prevost et al, 2011;Stuber et al, 2011). Bilateral amygdala and nucleus accumbens showed significantly greater response to wins than to losses in both adolescents and adults (Ernst et al, 2005).…”
Section: Reward Dependencementioning
confidence: 99%
“…Human electrophysiological studies showed a dynamic interaction between the striatum and medial frontal cortex underlying reward-guided learning and decision-making (Cohen, 2007;Cohen et al, 2009). The amygdala was reported to facilitate reward-seeking behaviors by the glutamatergic or dopaminergic neurotransmission in the amygdala-striatum pathway (Lintas et al, 2011;Prevost et al, 2011;Stuber et al, 2011). Bilateral amygdala and nucleus accumbens showed significantly greater response to wins than to losses in both adolescents and adults (Ernst et al, 2005).…”
Section: Reward Dependencementioning
confidence: 99%
“…The NAC has been heavily implicated in stress responses, mood disorders, and processing natural rewards 2,5,[11][12][13][16][17][18][19][20][21] . Moreover, pathophysiological dysfunction of the NAcc in response to various stressors has been implicated in anhedonia and reward conditioning [18][19][20][21] .…”
mentioning
confidence: 99%
“…Moreover, pathophysiological dysfunction of the NAcc in response to various stressors has been implicated in anhedonia and reward conditioning [18][19][20][21] . Our within-subject experiments revealed that, in the TST, the behavioral effects of optically reactivating DG cells labeled by a positive experience were blocked in the group of mice that concurrently received the glutamate receptor antagonists NBQX and AP5 in the NAcc, but not in the group that received saline, without altering basal locomotion (Extended Data Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations